2018
DOI: 10.1002/pros.23518
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic stromal inflammation is associated with bladder outlet obstruction in patients with benign prostatic hyperplasia

Abstract: The location of inflammation in the prostate might be an important factor affecting the severity of LUTS, especially voiding dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The sections were counterstained with haematoxylin‐eosin and inflammatory changes in the prostate and urinary bladder were assessed blindly by a pathologist (PUG). Histopathological analysis followed the same procedure as a previous study 18 that used a grading scale (Table 1) to categorize prostatic inflammation based on the magnitude or density of lymphocytes (grade) and the extent or distribution of lymphocyte infiltration (extent). The grade of prostatic and bladder inflammation was scored from 0 to 3 where 0 represented no inflammation and 3 represented severe inflammation (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sections were counterstained with haematoxylin‐eosin and inflammatory changes in the prostate and urinary bladder were assessed blindly by a pathologist (PUG). Histopathological analysis followed the same procedure as a previous study 18 that used a grading scale (Table 1) to categorize prostatic inflammation based on the magnitude or density of lymphocytes (grade) and the extent or distribution of lymphocyte infiltration (extent). The grade of prostatic and bladder inflammation was scored from 0 to 3 where 0 represented no inflammation and 3 represented severe inflammation (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…T A B L E 1 Grading scales of inflammatory changes in the prostate and bladder. The procedure for determination of grade and extent of inflammation were adapted from Inamura et al 18 Grade (inflammatory cell density, cells/mm 2 ) 30.17 ± 9.72, p = .046; control vs. Z14: 1.00 ± 0.31 vs. 33.40 ± 8.13, p = .033; control vs. Z21: 1.00 ± 0.31 vs. 35.83 ± 9.44, p = .014). No significant differences could be seen in regard to NVCs between the CPPS groups.…”
Section: Cystometrymentioning
confidence: 99%
See 1 more Smart Citation
“…By observing the TURP and HoLEP samples of 179 BPH patients, the patients were divided into stromal group and nonstromal groups according to whether or not the main site of chronic inflammation occurred in the stromal tissue. The stromal group was found to have a significantly larger total prostate volume (TPV) than the nonstromal group (63.8 vs. 53.8mL; P = 0:032), and the incidence of AUR was significantly increased (36.1% vs. 11.4%; P = 0:006) [31]. There were also significant differences in urinary indicators.…”
Section: The Role Of Inflammation In Bphmentioning
confidence: 96%
“…Chronic inflammation can be found in most BPH pathological specimens (11)(12)(13); thus, BPH has been regarded as an immune inflammatory disease (14)(15)(16). Relevant studies have confirmed that prostatic inflammation is strongly correlated with AUR in BPH patients (17)(18)(19)(20)(21)(22). Moreover, the severity of the inflammatory response is positively associated with both the occurrence of AUR and the requirement for surgical operations (23).…”
Section: Introductionmentioning
confidence: 99%